Menawarkan Pengaturan Tindakan Rehabilitasi Terhadap Pelaku Perilaku Menyimpang LGBT - Rifqi Daffa Saputra; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2025)
LGBT is an immoral phenomenon that threatens the security of society. This study aims to obtain information on the criminalization of LGBT behavior and the imposition of rehabilitation measures for such criminal acts. This study uses normative juridical research method with data obtained through literature study. The primary and secondary data collected are analyzed in a culaitative manner. The result of this research informs that LGBT behavior can be criminalized. Furthermore, rehabilitation measures are an effective form of punishment for LGBT criminal offenses.